American Marxism - Levin, Mark R. (Mark Reed), 1957- (Threshold Editions, 2021)
"In 2009, Mark R. Levin galvanized conservatives with his unforgettable manifesto Liberty and Tyranny, by providing a philosophical, historical, and practical framework for halting the liberal assault on Constitution-based values. That book was about standing at the precipice of progressivism's threat to our freedom and now, over a decade later, we're fully over that precipice and paying the price. In American Marxism, Levin explains how the core elements of Marxist ideology are now pervasive in American society and culture"--